The Battle for the Remote Control—Has the FCC Indecency Policy Worn Out its Welcome in America's Living Room? - Sarah Herman (Washington University Journal of Law & Policy, 2012)
The Supreme Court granted certiorari to decide whether the Federal Communications Commission‘s (the "FCC" or the "Commission") indecency policy violates the First and Fifth Amendments (Fox IV). Oral argument was heard on January 10, 2012. The case is on appeal from the Second Circuit, which struck down the FCC's indecency policy in Fox Television Stations, Inc. v. Federal Communications Commission (Fox III) as impermissibly vague in violation of free speech. Part I of this Note traces the history of the FCC‘s indecency policy. It discusses relevant technological advances that are useful in filtering television programming to safeguard children from indecent material. Part II of this Note examines the strengths and weaknesses of the FCC‘s indecency policy and the case law that has helped shape it into its current form. This analysis includes arguments for and against maintaining, eliminating, or modernizing the policy. Part III of this Note discusses my proposals for resolving the First Amendment and censorship issues arising from the FCC indecency policy as it stands today.
Keywords: Fox Television Stations; Inc. v. FCC 613 F.3d 317 (2d Cir. 2010); Decency standards; Freedom of speech; United States Constitution; United States